Equivalence Errors in Google Translate-Based Translation Results of Informative Text by Students of German Literature Department - Nur Atika Zahra; Rosyidah Rosyidah (Universitas Negeri Malang, 2021)
This research aims to describe the errors made by students when translating the informative text using Google Translate and to describe the role of Google Translate in the translation’s process. In this study, the two data were (1) the words and phrases containing equivalence errors in the translation results by the students and (2) the students’ statements showing the role of Google Translator in the translation’s process. The results showed that the students made two errors in translating the informative text, namely (1) misinterpretation and (2) non-equivalent context. Regarding the role of Google Translate, the student considered it as a helpful tool in the translation process. They stated that Google Translate helps in providing an overview of the source text and can reduce the translation time. The result showed that Google Translate can give an overview of the meanings of the source language but doesn’t shorten the translation time.